Robotic Urology (Springer International Publishing, 2018)
This updated edition offers guidance on the application of robotic surgery in urology. Each technique is described in detail, with careful explanation of the different surgical steps. The book brings together leading robotic surgeons from around the world and utilises their knowledge once again to update and provide a manual that covers all the oncologic and reconstructive procedures in urologic surgery that are performed with robotic assistance. This book serves as an ideal reference work for all urologists and should contribute in supporting new robotic teams.